Marico – competing with an innovative business model. Issue 2 (26th June 2018) - Mitra, Sumit; V.K., Ranjith
Abstract : Subject area: Strategic Management. Study level/applicability: MBA, Executive MBA. Case overview: This case deals with Harsh Mariwalla's struggle to develop an innovative company from scratch. The journey of innovation is not an easy one. Marico was forced to compete with multinationals in many markets where it operated. Constant pressure from rivals has made the company develop a new innovative business model, which is expected to generate profitability and sustainable competitive advantage. Expected learning outcomes: Students will be able to appreciate the business models, understand the competitive moves by rivals, understand strategy formulation and implementation, understand product innovation and competitive advantage and understand the ability to tackle competition with innovation. Supplementary materials: Teaching notes are available for educators only. Please contact your library to gain login details or email support@emeraldinsight.com to request teaching notes. Subject code: CSS 11: Strategy.